Al-Dunyā Sūratuhā Wa Haqīqatuhā Fī Al-Qur`ān Al-Karīm (Dirāsaħ Maudūiyyah): الدنيا صورتها وحقيقتها في القرآن الكريم (دراسة موضوعية) - Muhammad Salman Al-Farisy; Wildan Fata Mubarok; Lira Erlina (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2021)
This study aims for a firm confrontation that posits concepts (life/world) that go beyond the Qur'an and concepts in worldly life, namely facing the plurality of ignorance that causes the decline of this people. The study takes an objective descriptive approach by examining the words of the world contained in the Qur'an, then collecting them, classifying them, presenting them, and analyzing them in both image and reality. This study proves that the essence of muamalah with the world requires a healthy mind and a clear heart of luxury and desire, not with an unconscious mind and a hard heart, and this is the purpose of this research and as a reminder to all of us.